(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In the article the detailed analysis of the "woman" concept in Russian and Kazakh languages is presented. The full nominative paradigm of words, where all zones are characterized, is given. Illustrative examples of the using the concept in polylingual, in particular, Russian-Kazakh newspapers are given. At the end of the article the forecasts of nominative activity’s development of these words and potential narrowing/expansion of borders of the concept are given. The material, as lexicographic recorded (statics), and not reflected in the dictionaries, but actively being applied in the modern Kazakhstan mass media (dynamics) was used. On the basis of the obtained data the conclusion about the different place of the woman in cognitive (mental) space of carriers of Russian and Kazakh languages is drawn.